The relationship between technological capability and innovative SMEs - Mohd Radzi, Noorhassidah (2020)
Rapid changes in market condition, seen small and medium enterprises (SMEs) give major impact to Malaysian economy because it has provided a great contribution to the economy. Despite the importance of SMEs and the existence of government support from the various ministries and agencies, most literature indicated that SMEs are still having a lot of challenges that hinder their development. This research suggests the embracing of technological capability as an approach to enhance SMEs competitiveness. The objectives of this research are to identify the practices of technological capabilities among innovative SMEs in Malaysia and to investigate the relationship between technological capability and entrepreneurial orientation. The research adapted survey research design using questionnaire to obtain the quantitative data and simple random sampling was used to select the respondents. There are 51 respondents with 86% of response rate companies which are Malaysian innovative SMEs and listed under MTDC incubator programme. The data was analysed using IBM SPSS Software. Descriptive analysis, correlation and regression analytical techniques were used in analysing the research data. The findings indicated that the average mean score for the parameters of technological capability is at high level. This indicates that innovative SMEs that participated in this research have successfully practiced technological capability in their organization. The result of the hypothesis testing show an inter-item correlation that depicts positive correlation with significant relationship between innovation capability and investment capability to entrepreneurial orientation. However, there are no correlation exists between production capability with entrepreneurial orientation. This result indicate that SME entrepreneurs should understand and be aware of the importance of both organizational context and behavioural complexity in developing firm related capabilities in order to achieve the desired level of manufacturing flexibility thus boost their production more efficiently and effectively. Overall, firms need to perform an internal strategic and coherent strategy commensurate with the expected environment to get better performance.